2001
DOI: 10.1002/rcm.290
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput cytochrome P450 (CYP) inhibition screening via a cassette probe‐dosing strategy. VI. Simultaneous evaluation of inhibition potential of drugs on human hepatic isozymes CYP2A6, 3A4, 2C9, 2D6 and 2E1

Abstract: The inhibition potential of drugs towards five major human hepatic cytochrome P450 (CYP) isozymes (CYP2A6, 3A4, 2C9, 2D6, and 2E1) was investigated via cassette dosing of the five probe substrates (coumarin, midazolam, tolbutamide, dextromethorphan, and chlorzoxazone) in human liver microsomes using a 96-well plate format. After microsomal incubations had been terminated with formic acid, the five marker metabolites (7-hydroxycoumarin, 1'-hydroxymidazolam, 4-hydroxytolbutamide, dextrorphan, and 6-hydroxychlorz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 15 publications
3
53
0
1
Order By: Relevance
“…Although strategies have been developed to increase throughput by techniques such as sample pooling, multiple assay compression, high-speed LC/MS (Bu et al, 2001;Zhang et al, 2002), single-concentration IC 50 projection (Gao et al, 2002), and virtual screening (Rao et al, 2000;Zuegge et al, 2002), the analytical approach still remains a challenge that limits sample throughput.…”
mentioning
confidence: 99%
“…Although strategies have been developed to increase throughput by techniques such as sample pooling, multiple assay compression, high-speed LC/MS (Bu et al, 2001;Zhang et al, 2002), single-concentration IC 50 projection (Gao et al, 2002), and virtual screening (Rao et al, 2000;Zuegge et al, 2002), the analytical approach still remains a challenge that limits sample throughput.…”
mentioning
confidence: 99%
“…Currently, the most widely employed incubation sample preparation is protein precipitation (PPT) [11][12][13][14][15][16][17][18][19]. Our initial approach for sample preparation was based on PPT, while it was found that liquid-liquid extraction provided a 10-fold higher sensitivity for the majority of the CYP probe substrate metabolites than PPT.…”
Section: Sample Preparationmentioning
confidence: 99%
“…At present, numerous high-throughput approaches using fluorogenic substrates to measure CYP activities have been described [8,9], as well as substrate "cocktail" experiments that simultaneously measure more than one CYP activity [10][11][12][13][14][15][16][17][18]. Recently Kim et al [19] described a high-throughput method that allowed the simultaneous evaluation of the metabolic activities of nine major human CYP isoforms (i.e., CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1, and CYP3A4) on their well-known specific probe substrates using human hepatic microsomes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to estimate the metabolism in the human body, human liver microsomal preparations are often used to evaluate the in vitro metabolism of the lead compound. 168,169 LC/MS/MS using a triple quadrupole instrument is an appropriate and powerful means for that purpose. The full-scan mode can easily provide information on changes in the molecular weight due to metabolism; in addition, the neutral loss scan and precursor scan, which are unique to the MS/MS instrument, can also easily identify the metabolites in most contaminants.…”
Section: ·2 Drug Metabolismmentioning
confidence: 99%